Proceedings of the 32nd ACM/IEEE International Conference on Software Engineering - Volume 1 2010
DOI: 10.1145/1806799.1806870
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of reported bugs in server software with implications for automated bug diagnosis

Abstract: Reproducing bug symptoms is a prerequisite for performing automatic bug diagnosis. Do bugs have characteristics that ease or hinder automatic bug diagnosis? In this paper, we conduct a thorough empirical study of several key characteristics of bugs that affect reproducibility at the production site. We examine randomly selected bug reports of six server applications and consider their implications on automatic bug diagnosis tools. Our results are promising. From the study, we find that nearly 82% of bug sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The role of software users and essential information in bug-fixing has been emphasized in several studies [1,2,25,31]. Bettenburg et al [1] found that there is usually a strong mismatch in bug reports between what developers need to reproduce and fix a bug and what is provided by users.…”
Section: Related Workmentioning
confidence: 99%
“…The role of software users and essential information in bug-fixing has been emphasized in several studies [1,2,25,31]. Bettenburg et al [1] found that there is usually a strong mismatch in bug reports between what developers need to reproduce and fix a bug and what is provided by users.…”
Section: Related Workmentioning
confidence: 99%
“…The inputs from the bug reports we used in experiments were small but not necessarily minimal. An earlier empirical study [37] of over 260 randomly selected bugs in six different server applications (including some stateful servers) found that most bugs could be reproduced with 3 or fewer inputs. If the inputs are very large, tools like ddmin [45], delta debugging [12,44], and C-Reduce [36] do a good job of minimizing the inputs for many classes of applications.…”
Section: Good and Bad Input Constructionmentioning
confidence: 99%
“…Fonseca et al [8] expressed that many such studies centered around the causes (i.e., error propagation chains) of the studied concurrency bugs, and they [8] studied the effects of concurrency bugs. Sahoo et al [22] found that many concurrency bugs reported in the opensource bug repositories of the selected server applications could not be reproduced deterministically, and these reproducible bugs only constituted a small portion of all the bug records they have examined.…”
Section: Related Workmentioning
confidence: 99%